Subtitle Accuracy for Children in Translating Cartoon from English into Indonesia - Istiqomah, Lilik; Azizah, Nada Nur; Rahmah, Farah Mufidah (English Education: Jurnal Tadris Bahasa Inggris, 2020)
The objectives of the research are to classify the accuracy in translating cartoon  from  English  to Indonesian  subtitles,  to  determine  the  accuracy  and readability of translating English to Indonesian subtitles of Tayo Cartoon movie by the amateur translator. This research is a descriptive qualitative method. Data of this research are utterances or sentences in subtitle movies of the bilingual edition, both English and Indonesian. Meanwhile, the source of the data is Tayo Cartoon movie. In analyzing the data, researchers used a comparison method to compare Source Language (SL) and Target Language (TL). This research shows that the subtitle made by the subtitling class students as the amateur translator acceptable for the children with some reconciliation from SL into TL. In conclusion, it can be concluded that the translation quality of Tayo Cartoon movie by the subtitling class students as the amateur translator is accurate.